218k views
4 votes
9. Combine the radical expression, if possible.

9. Combine the radical expression, if possible.-example-1
User Tim Rogers
by
5.5k points

1 Answer

6 votes

Answer:

we conclude that:


3√(125)+4√(20)=23√(5)

Hence, the last option i.e.
23√(5) is correct.

Explanation:

Given the expression


3√(125)+4√(20)

Combining the radical expressions


3√(125)+4√(20)

let us first solve


3√(125)


=3√(5^3)


=3√(5^2\cdot \:5)

Apply radical rule:
√(ab)=√(a)√(b),\:\quad \:a\ge 0,\:b\ge 0


=3√(5^2)√(5)

Apply radical rule:
√(a^2)=a,\:\quad \:a\ge 0


=3\cdot \:5√(5)


=15√(5)

Thus,


3√(125)=15√(5)

similarly solving


4√(20)


=4√(2^2\cdot \:5)

Apply radical rule:
√(ab)=√(a)√(b),\:\quad \:a\ge 0,\:b\ge 0


=4√(2^2)√(5)

Apply radical rule:
√(a^2)=a,\:\quad \:a\ge 0


=4\cdot \:2√(5)


=8√(5)

Thus,


4√(20)=8√(5)

so we get


3√(125)=15√(5)


4√(20)=8√(5)

so the expression becomes


3√(125)+4√(20)=15√(5)+8√(5)
3√(125)=15√(5) ,
4√(20)=8√(5)


=23√(5)
15√(5)+8√(5)=23√(5)

Therefore, we conclude that:


3√(125)+4√(20)=23√(5)

Hence, the last option i.e.
23√(5) is correct.

User Matt Nibecker
by
6.4k points